BIMBINGAN PRANIKAH DI KANTOR URUSAN AGAMA (KUA) KECAMATAN KAPUR IX - Enjela Pulda Putri; Hidayani Syam (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study was to find out how the implementation of Premarital Guidance at the Office of Religious Affairs (KUA) of Kapur IX District and what materials were given by religious counselors at KUA of Kapur IX District during premarital guidance. The research method that the author uses in writing this article is a descriptive qualitative research method with data collection techniques through observation, documentation, and interviews. The sources of data from this study were extension workers at KUA Kapur IX District and books related to this research. The results of this study indicate that the implementation of Premarital Guidance at the KUA of Kapur IX District is carried out every Thursday starting at 10.00 WIB until it is finished. The methods used in providing premarital guidance to the bride and groom are lecture, discussion, and question and answer methods. In the implementation of premarital guidance at KUA Kapur IX District there were several supporting and inhibiting factors in achieving the successful implementation of the premarital guidance. The supporting factors are the willingness of the bride and groom, adequate facilities and infrastructure, and professional extension workers. And the inhibiting factor in the implementation of premarital guidance is that there are still prospective brides who are not punctual in following the guidance and there are still prospective brides who consider this premarital guidance not so important. The pre-marital guidance material given by the counselor to the bride and groom is material about the purpose of marriage, husband and wife's obligations, attitudes that support the realization of a happy/sakinah family, rules for husband and wife association, first night etiquette, mandatory bathing, times when it is forbidden to associate with the husband wife, things that are prohibited in the household, things that can disturb the harmony of the household, and so on.